If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(9 + -4y) = 5y (9 * -1 + -4y * -1) = 5y (-9 + 4y) = 5y Solving -9 + 4y = 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -9 + 4y + -5y = 5y + -5y Combine like terms: 4y + -5y = -1y -9 + -1y = 5y + -5y Combine like terms: 5y + -5y = 0 -9 + -1y = 0 Add '9' to each side of the equation. -9 + 9 + -1y = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1y = 0 + 9 -1y = 0 + 9 Combine like terms: 0 + 9 = 9 -1y = 9 Divide each side by '-1'. y = -9 Simplifying y = -9
| x-5=-35 | | z^3+250=250i | | 12x-4=2x+26 | | x^2+10x-252=0 | | -x+2=10 | | 3t^2-12t+8=0 | | -12=28-4b | | 5y=2(4-2y) | | 5x+7-4x=8 | | 3m-9+-1=24 | | 2x^2-9=x^2 | | 7=-2(3y-5) | | 6(6x-7)=-86 | | 12x^2-42x+8=0 | | m+3+1=7 | | U^2+5uv+6v^2=0 | | 2x/3+x/2=7 | | 5x^2+3=0 | | 2*(x+5)=3*(2x-7)+15 | | 0.26(2.39x-4.91)=10.64 | | 8x+5+7-2x=q | | 4--4y+3y=1 | | (2x+8)(x)=2170 | | X^3-9x^2+22x-14=0 | | 31-2h/(-7)=-9 | | x+3=2x-9 | | (180-x)-(90-x)=90 | | 3(x-5)+1=34 | | 4A+10= | | -8=y-1/0-(-2) | | 3(y+8)=5y+4 | | -x+7=0 |